2014
DOI: 10.1080/01635581.2015.976320
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive and Therapeutic Potential of “Naringenin,” a Flavanone Present in Citrus Fruits

Abstract: Cancer is one of the major causes of deaths in developed countries and is emerging as a major public health burden in developing countries too. Changes in cancer prevalence patterns have been noticed due to rapid urbanization and changing lifestyles. One of the major concerns is an influence of dietary habits on cancer rates. Approaches to prevent cancer are many and chemoprevention or dietary cancer prevention is one of them. Therefore, nutritional practices are looked at as effective types of dietary cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 140 publications
1
52
0
1
Order By: Relevance
“…Epidemiological studies have demonstrated that the consumption of vegetables and fruit with a high Nar content, such as citruses and tomatoes or their food products, is associated with a reduced incidence of metabolic and chronic-degenerative diseases 1, 2 . Following this kind of evidence, several in vitro studies have shown that Nar interacts with various cellular pathways, highlighting its potential as an antioxidant, antinflammatory, chemopreventive and antidegenerative agent 3 ; moreover, Nar was shown to exert anti-angiogenic effects in the avian chorio-allantoid membrane model 4 while this manuscript was being prepared. Naringenin lowers the plasma and hepatic cholesterol concentrations by suppressing HMG-CoA reductase and ACAT in rats fed a high-cholesterol diet 5 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Epidemiological studies have demonstrated that the consumption of vegetables and fruit with a high Nar content, such as citruses and tomatoes or their food products, is associated with a reduced incidence of metabolic and chronic-degenerative diseases 1, 2 . Following this kind of evidence, several in vitro studies have shown that Nar interacts with various cellular pathways, highlighting its potential as an antioxidant, antinflammatory, chemopreventive and antidegenerative agent 3 ; moreover, Nar was shown to exert anti-angiogenic effects in the avian chorio-allantoid membrane model 4 while this manuscript was being prepared. Naringenin lowers the plasma and hepatic cholesterol concentrations by suppressing HMG-CoA reductase and ACAT in rats fed a high-cholesterol diet 5 .…”
Section: Introductionmentioning
confidence: 91%
“…Naringenin lowers the plasma and hepatic cholesterol concentrations by suppressing HMG-CoA reductase and ACAT in rats fed a high-cholesterol diet 5 . Pre-clinical studies have revealed the potential of Nar and of its precursor naringin in the treatment of metabolic and cardiovascular disorders, including hyperlipidemia, hypertension, cardiac toxicity, hyperglycemia and diabetes, hepatic steatosis and atherosclerosis 2 ; its therapeutic use to combat various kinds of cancer has also been envisaged 3 . Indeed, Nar exerts chemopreventive and anticancer activity by blocking the progression and the formation of metastasis in various experimental models of oral 6 , melanoma 7 , breast 8, 9 , colon 10 , lung 11 and liver 12 cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, its lipophilic character favors a good blood-brain barrier (BBB)-permeability, which suggests that naringenin could play a significant role in important functions of the CNS especially under pathological conditions. For example, naringenin exerts protective effect against cerebral ischemic injury, attenuates bamyloid toxicity [17], induces the activation of MAP kinases, modulates glutamate uptake [18] and protects against neurodegeneration with cognitive impairment caused by the intracerebroventricular-streptozotocin in diabetic oxidative damage rat model [19]. However, the mechanisms underlying the neuroprotective effects of naringenin on cholinergic and purinergic neurotransmission in animal models of iron exposure remain unknown.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, shikonin triggers necrosis and apoptosis in gastric cancer cells (8). Furthermore, a bioactive compound isolated from citrus called naringenin has been revealed to trigger apoptosis and inhibit migration in cancer cells (9). Treatment with naringenin resulted in apoptosis by activation of the p38 mitogen-activated protein kinase and caspase 3 pathway in cancer cells that expressed estrogen receptor a or b (10).…”
Section: Introductionmentioning
confidence: 99%